Challenges in facilitators’ professional development – complexities within a scaling up process as reasons for dropout - Scherer, Petra; Rolka, Katrin (Frontiers in Education, 2024)
In-service courses for teachers are often provided by so called facilitators who function as teacher trainers and whose tasks in the education system are multifaceted. The professional development (PD) of facilitators is of great importance, and the complex process of scaling up might lead to unexpected constraints, and influence the effectiveness of a program. In general, more research is needed concerning facilitators’ PD with respect to their different roles and functions. In this paper, a project will be presented that focused on qualifying facilitators for the topic ‘inclusive mathematics’ and accompanied the process of scaling up. In the end, unexpectedly, five out of 15 facilitators did not finish the program. Therefore, the challenges and concrete reasons for dropout were investigated in detail. The paper will present a case analysis, where Facilitators’ multifaceted roles, functions, and tasks emerged as the central category. Moreover, conclusions for professionalization programs and research will be derived and discussed.